Impact Of Quality Factors On E-Procurement Success Of Iranian Automotive Industries - Eskandarian, Mahnaz (2015)
This study presents a model to conduct an empirical e-procurement quality model to increase the probability of the e-procurement adoption and implementation in the automobile industry of Iran. More than 50% of the e-procurement application fail in Iran, in which using e–business in the different aspects of the Iran's industry seems so crucial. Automobile manufacturing is vital to Iran's economy; therefore, this research examines the e-procurement quality model on car industry in Iran. Critical success factors of e-procurement help e-procurement succeed when most e-procurement installations and applications still fail. A previous research studied the role of quality of material and information flow for productive practice and success of e-procurement process, which is not still enough for the successful adoption and implantation of this process.